Terminal value problems of impulsive integro-differential equations in Banach spaces. (1997) - Guo, Dajun
Abstract : This paper uses cone theory and the monotone iterative technique to investigate the existence of minimal nonnegative solutions of terminal value problems for first order nonlinear impulsive integro-differential equations of mixed type in a Banach space.